Genome Mutational and Transcriptional Hotspots Are Traps for Duplicated Genes and Sources of Adaptations. (1st May 2017) - Fares, Mario A.; Sabater-Muñoz, Beatriz; Toft, Christina
Abstract : Gene duplication generates new genetic material, which has been shown to lead to major innovations in unicellular and multicellular organisms. A whole-genome duplication occurred in the ancestor of Saccharomyces yeast species but 92% of duplicates returned to single-copy genes shortly after duplication. The persisting duplicated genes in Saccharomyces led to the origin of major metabolic innovations, which have been the source of the unique biotechnological capabilities in the Baker's yeast Saccharomyces cerevisiae . What factors have determined the fate of duplicated genes remains unknown. Here, we report the first demonstration that the local genome mutation and transcription rates determine the fate of duplicates. We show, for the first time, a preferential location of duplicated genes in the mutational and transcriptional hotspots of S. cerevisiae genome. The mechanism of duplication matters, with whole-genome duplicates exhibiting different preservation trends compared to small-scale duplicates. Genome mutational and transcriptional hotspots are rich in duplicates with large repetitive promoter elements. Saccharomyces cerevisiae shows more tolerance to deleterious mutations in duplicates with repetitive promoter elements, which in turn exhibit higher transcriptional plasticity against environmental perturbations. Our data demonstrate that the genome traps duplicates through the accelerated regulatory and functional divergence of their gene copies providing a source of novel adaptations in yeast.